ADDUCTOR SQUEEZE TESTING IN SOCCER: PRECISION, TORQUE PRODUCTION & IMPLICATIONS FOR SCREENING. Issue 22 (1st November 2016) - Light, N; Thorborg, K
Abstract : Reduced adductor strength is a known risk factor for groin injury amongst footballers. Team clinicians often test the adductor strength of players using isometric squeeze tests, performed regularly during the season to monitor fluctuations in scores. Various positions of testing are commonly used but it is not clear on which are the most reliable, stressful and ultimately capable of detecting subtle deficits in strength. In this study, three common adductor squeeze tests (long-lever, short lever in adduction and short lever-in abduction/external rotation) were investigated for differences in reliability and torque production. Using a test-retest reliability and cross-sectional comparison design, twenty professional footballers (16–33 years) without previous or current groin pain, performed a series of isometric squeeze tests measured by hand-held dynamometry. The tests were performed on two test days separated by two weeks, with both relative and absolute reliability determined, alongside torque production. Results showed no systematic variation for any of the tests, when the mean of three measures was used (ICC=0.84–0.97, MDC%=6.6–19.5). However, the least variation was observed using the long-lever position (ICC=0.97, MDC%=6.6), which also generated higher mean torque values when compared with short-lever in adduction (69%) and short lever in abduction/external rotation (11%) positions (p<0.001). In conclusion, all three tests described in this study are reliable methods of measuring adductor squeeze strength. However, long-lever squeeze testing displayed the highest adductor torque production and test-retest precision. Both of these test attributes are arguably vital for squeeze test monitoring, in order to confidently detect clinically meaningful deficits in scores that may predispose a player to subsequent injury.